2020
DOI: 10.1186/s12885-020-06851-z
|View full text |Cite
|
Sign up to set email alerts
|

Cytology cell blocks from malignant pleural effusion are good candidates for PD-L1 detection in advanced NSCLC compared with matched histology samples

Abstract: Background: Detection of programmed cell death ligand-1 (PD-L1) by immunohistochemistry (IHC) has been commonly used to predict the efficacy of treatment with PD-1/PD-L1 inhibitors. However, there is limited literature regarding the reliability of PD-L1 testing using malignant pleural effusion (MPE) cell blocks. Here, we assess PD-L1 expression in sections from MPE cell blocks and evaluate the value of IHC double staining in the interpretation of PD-L1 expression. Methods: In all, 124 paired formalin-fixed tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 40 publications
(58 reference statements)
1
14
2
Order By: Relevance
“…The lower PD-L1 concordance seen for our PE cytology, which is in contrast with some studies [32,33], may be attributed to one or more several factors. The PE samples represent metastases while all biopsies in our cohort were from the primary tumour.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The lower PD-L1 concordance seen for our PE cytology, which is in contrast with some studies [32,33], may be attributed to one or more several factors. The PE samples represent metastases while all biopsies in our cohort were from the primary tumour.…”
Section: Discussioncontrasting
confidence: 99%
“…The studies by Grosu et al [32] and Zou et al [33] reported a rather high PD-L1 concordance between histological specimens and PE cell blocks, with weighted κ values of 0.76 and 0.77, respectively, for PD-L1 <1% vs. 1-49% vs. ≥50% (the corresponding weighted κ was 0.25 in our PE subgroup). One obvious difference compared to our study is the mixture of biopsies and resections as histological specimens in these studies.…”
Section: Discussionsupporting
confidence: 55%
“…Our finding indicated that only 3 out of 84 samples show true difference in PD‐L1 staining between single staining and double staining in either cytopathology or histopathology specimens, all of them showing staining accentuation in double staining. This is in contrast to the results reported by Zou et al, 16 who claimed that double‐staining with TTF‐1 resulted in a “general decrease” of PD‐L1 staining in tumor cells. Important differences between the current study and the Zou et al study include the anti–TTF‐1 antibody used (clone SP141 vs clone SPT24, respectively), difference in staining protocol, and absence of a cytotechnologist double‐check in the study by Zou et al More research from different laboratories is required to clarify this important issue.…”
Section: Discussioncontrasting
confidence: 99%
“…Grosu et al [50] and Zou et al [57] showed a higher concordance for PD-L1 in pleural effusions compared to matched histological samples (87–97% at 1% cutoff) than did Yoshimura et al [37] and Jug et al [58] for EBUS-guided samples (70–84%). Such a trend is not seen when comparing our 2 cohorts but may be concealed by other differences with greater impact.…”
Section: Discussionmentioning
confidence: 99%